A Review of Field Experiments in Planning and Urban Research. (20th October 2019) - Honey-Rosés, Jordi
ABSTRACT: Experimental methods remain largely underused by planning researchers and professionals. By adopting experimental research designs, urban scholars and practitioners can develop research programs that test theory, measure impact, build evidence, and learn about key relationships. While not all planning policies are amenable to experimentation, there is untapped potential to apply experimental approaches in many contexts. This paper aims to generate enthusiasm for experimental research methods in planning practice and scholarship by illustrating how experiments have been used to examine relevant urban questions.